Investigating the Signal Strength in Digital Terrestrial Television Broadcasting Network: A case study in Ashanti Region - A. Dotche, K.; Sibiri Bayor, W-N.; K. Ofosu, Willie; Diawuo., K (International Journal of Engineering and Technology, 2018)
This paper presents an investigation on the distribution of the signal strength in digital terrestrial television broadcasting network in Ashanti region. The work intends to identify the feasibility limits of implementing the mobile digital television (DTT) network. A review on signals measurement both on small and large scale fading models used in the design are given in addition to the theory of signal distribution characteristics. It proceeds on signal characteristics using the distribution functions methods in order to predict the type of small-scale fading distributions that could characterize a given digital TV signal. The signal strength was obtained through measurement using a field strength meter. The Matlab software was used to analyse the data for the analysis.The obtained results are much mitigated, but though they agree with some similar results obtained in the sub-region. We strongly believe that data span over large length would ultimately lift the clear picture of the small-scale fading distribution characteristics and the proposition to improve the theoretical model.Â